The influence of water intake on waiting time prior to uroflowmetry: a prospective, randomized, double-blind trial (Faculty of Medicine Universitas Indonesia, 2017)
Background: In uroflowmetry examination, patients are usually instructed to intake a large volume of water and wait until the bladder is full. The association between the volume of water intake and the waiting time before uroflowmetry is unknown. The aim of this study is to investigate the relationship between the volume of water intake and the waiting time prior to uroflowmetry. Methods: This trial was designed as a randomized, researchers, caregivers and patients blinded, superiority trial with three parallel groups and primary endpoint of waiting time prior to the uroflowmetry study based on the volume of patients' water intake. Randomization was performed by block randomization with a 1:1:1 allocation. Patients scheduled for uroflowmetry at the Urology Clinic of Cipto Mangunkusumo Hospital were enrolled from March 2013 until December 2013. The eligibility criteria were male patients with ages above 50 years and body mass index 18.5-24.9 kg/m2. Results: A total of 83 patients was randomly assigned into 3 study groups: 300 ml (28 patients), 400 ml (28 patients), and 500 ml (27 patients). All patients were included in final analysis. Mean waiting time were 85.1±59.8 min, 107.2±70.4 min, and 66±28.4 min for patients intake 300, 400, and 500 ml of water respectively (p=0.07). The final bladder volumes for three groups were statistically different (262.4±130.8 ml, 289.4±126.2 ml, 359.2±137 ml; p=0.02). Conclusion: The volume water intake of 300-500 ml did not affect waiting time before uroflowmetry. Increasing water intake at least 500 ml added the final bladder volume and shorter the waiting time.